The effect of revenue planning on municipal financial performance: a case study of the Polokwane Local Municipality in the Limpopo Province - Molobela, T. T. (SAAPAM (South African Association of Public Administration and Management), 2016)
There are recent findings that signify municipal consumer debt and revenue planning as problematic in the South African local government system. This is caused by non-payment of municipal services partly due to poverty and ever-increasing unemployment in the local communities. Despite these challenges municipalities remain obligated to provide services to communities as they are mandated in the Constitution of the Republic of South Africa, 1996. Revenue planning develops critical approaches to achieve effective financial performance in municipalities. Financial performance in turn grants municipalities with the ability to render services to its concerned citizens. The paper investigates the effects of revenue planning on municipal financial performance in the Polokwane Local Municipality. The study focuses on the Polokwane Local Municipality in the Limpopo Province, because this municipality is the heartbeat and backbone of an emerging city of Polokwane. Furthermore, the paper argues that revenue planning and financial performance of the municipality requires a holistic approach. This is because amongst other things, there is minimal ward committee's involvement in the revenue planning process; there's lack of constant training to address identified financial issues, non-payment of municipal services and the culture of non-payment of service seems to grow rapidly particularly in rural communities. Despite the issue of non-payment, the municipality implement water and electricity restrictions where customers fail to settle their debts. The study is qualitative in nature. In its investigation face-to-face interviews will be conducted with municipal officials. The findings of the study will significantly contribute to the understanding of the implication of municipal revenue planning on the financial performance. The study concludes by recommending the development of proficiency through separated training material and programmes with regard to municipal revenue planning on financial performance, and the involvement of role players in the revenue planning process, as well as the employment of good strategic methods of raising adequate municipal revenue.
Article
Keywords: Revenue planning; Financial performance; Municipal revenue -- South Africa -- Limpopo; Municipal finance -- South Africa -- Limpopo; Municipal government -- South Africa -- Limpopo